USP13 negatively regulates antiviral responses by deubiquitinating STING - Sun, He (Nat Commun, 2017)
STING (also known as MITA) is critical for host defence against viruses and the activity of STING is regulated by ubiquitination. However, the deubiquitination of STING is not fully understood. Here, we show that ubiquitin-specific protease 13 (USP13) is a STING-interacting protein that catalyses deubiquitination of STING. Knockdown or knockout of USP13 potentiates activation of IRF3 and NF-κB and expression of downstream genes after HSV-1 infection or transfection of DNA ligands. USP13 deficiency results in impaired replication of HSV-1. Consistently, USP13 deficient mice are more resistant than wild-type littermates to lethal HSV-1 infection. Mechanistically, USP13 deconjugates polyubiquitin chains from STING and prevents the recruitment of TBK1 to the signalling complex, thereby negatively regulating cellular antiviral responses. Our study thus uncovers a function of USP13 in innate antiviral immunity and provides insight into the regulation of innate immunity.